2020
DOI: 10.1182/blood.2019002783
|View full text |Cite
|
Sign up to set email alerts
|

Acetylsalicylic acid inhibits intravascular coagulation during Staphylococcus aureus–induced sepsis in mice

Abstract: Antiplatelet therapies have been proposed for the treatment of sepsis, a syndrome resulting from a dysregulated immune response and inappropriate activation of coagulation. Acetylsalicylic acid (ASA) may serve as a potential therapeutic strategy to prevent infection-induced coagulopathy and associated tissue damage. Using intravital microscopy, we found that Staphylococcus aureus infection induced neutrophil recruitment, platelet aggregation, and neutrophil extracellular trap (NET) release in the liver. Mice p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 23 publications
2
29
0
Order By: Relevance
“…The presence of smaller lesions in the mirtazapine-treated animals led us to assess vascular perfusion following S. aureus infection. Previous work has shown that infection-induced coagulation leads to vascular occlusion and associated tissue damage (27,28). Infection of mirtazapine-treated animals resulted in fewer occluded sinusoids ( Figure 5D), confirming reduced liver damage was associated with improved perfusion and less infection-induce coagulation.…”
Section: Mirtazapine-treatment Reduces Infection-induced Liver Damagesupporting
confidence: 64%
See 1 more Smart Citation
“…The presence of smaller lesions in the mirtazapine-treated animals led us to assess vascular perfusion following S. aureus infection. Previous work has shown that infection-induced coagulation leads to vascular occlusion and associated tissue damage (27,28). Infection of mirtazapine-treated animals resulted in fewer occluded sinusoids ( Figure 5D), confirming reduced liver damage was associated with improved perfusion and less infection-induce coagulation.…”
Section: Mirtazapine-treatment Reduces Infection-induced Liver Damagesupporting
confidence: 64%
“…We have previously demonstrated sinusoidal occlusion as the key driver in localized liver damage following infection (27,28). Thus, is it likely the reduced liver necrosis observed in mirtazapine-treated animals is associated with reduced vascular occlusion.…”
Section: Discussionmentioning
confidence: 97%
“…Provided that S. aureus cannot internalize into epithelial cells to hide from the immune system in presence of LASAG, a combinatory antibiotic therapy might be an efficient alternative. Beyond that, LASAG is also reported to prevent infection-induced coagulopathy and associated tissue damage [41]. Thus, its administration during secondary bacterial infection might be another benefit.…”
Section: Discussionmentioning
confidence: 99%
“…83,84 However, in other studies, blocking NET formation in animal models of sepsis reduced liver injury, improved liver (micro)perfusion and function, and did not result in increased bacterial dissemination. 28,40,85 In these models of sepsis, it was suggested that the loss of immune protection provided by NETs was offset by a gain of function by other immune cells in the liver. It has been shown that mice in which NETs were degraded (DNase treatment) had preserved immune function, with KCs and splenic macrophages compensating for the loss of immunoprotection attributed to NETs.…”
Section: Diagnostic Modalities and Future Therapeutic Strategiesmentioning
confidence: 99%